New Labor — New Challenges - Lyubov Lebedintseva; Ruben Karapetyan; Aleksandr Gonashvili; Snezhana Starovoitova; Stepan-Arseniy Karapetyan (Journal of Economic Sociology, 2018)
This article presents an overview of the key issues discussed at the Scientific Conference in the sessions ‘Labor and employment problems: new challenges and prospects’ and ‘Information economy and labor,’ This article presents an overview of the key issues discussed at the Scientific Conference in the sessions ‘Labor and employment problems: new challenges and prospects’ and ‘Information economy and labor’, held within the framework of the Second St. Petersburg International Youth Labor Forum which was conducted in St. Petersburg on February 28, 2018. The article describes the main ideas discussed at the conference. The main leitmotif of the presentations was the idea that the modern understanding of the problems of labor is very diverse. Young professionals entering the modern Russian labor market face a huge list of problems. The key issues on which speakers constantly focused their attention were the impact of new information realities on the sphere of work, the employment of young professionals in the context of changing labor market demands, and the dissemination of competence-oriented criteria for assessing the quality of specialists. Participants also discussed the dynamics of graduate employment, creativity and flexibility in the demand and development of intellectual work, training in the workplace, and many other areas. The general conclusion of the review, summarizing the work of the Scientific Conference sessions, was that young people want and will be ready for the challenges of the 21st century work context held within the framework of the Second St. Petersburg International Youth Labor Forum which was conducted in St. Petersburg on February 28, 2018. The article describes the main ideas discussed at the conference. The main leitmotif of the presentations was the idea that the modern understanding of the problems of labor is very diverse. Young professionals entering the modern Russian labor market face a huge list of problems. The key issues on which speakers constantly focused their attention were the impact of new information realities on the sphere of work, the employment of young professionals in the context of changing labor market demands, and the dissemination of competence-oriented criteria for assessing the quality of specialists. Participants also discussed the dynamics of graduate employment, creativity and flexibility in the demand and development of intellectual work, training in the workplace, and many other areas. The general conclusion of the review, summarizing the work of the Scientific Conference sessions, was that young people want and will be ready for the challenges of the 21st century work context.